Genetic Testing in Various Neurodevelopmental Disorders Which Manifest as Cerebral Palsy: A Case Study From Iran - Nejabat, Marzieh; Inaloo, Soroor; Sheshdeh, Afsaneh Taghipour; Bahramjahan, Shima; Sarvestani, Fatima Masoomi; Katibeh, Pegah; Nemati, Hamid; Tabei, Seyed Mohammad Bagher; Faghihi, Mohammad Ali (Frontiers in Pediatrics, 2021)
Purpose: Cerebral palsy (CP) is a heterogeneous permanent disorder impacting movement and posture. Investigations aimed at diagnosing this disorder are expensive and time-consuming and can eventually inconclusive. This study aimed to determine the diagnostic yield of next generation sequencing in patients with atypical CP (ACP). Methods: Patient eligibility criteria included impaired motor function with onset at birth or within the first year of life, and one or more of the following conditions: severe intellectual disability, positive family history, brain imaging findings not typical for cerebral palsy, abnormal neurometabolic profile, intractable seizure ,normal neuroimaging despite severe psychomotor disability, after pediatric neurologist assessment including neuroimaging and biochemical-metabolic study offered for genetic study. Results: Exome sequencing was done for 66 patients which revealed pathogenic, likely pathogenic, and variants of unknown significance in 36.2%, 9%, and 43.9%, respectively. We also found 10 new mutations and were able to suggest specific and personalized treatments for nine patients. We also found three different mutations with different phenotypical spectrum in one gene that have not been reported for cerebral palsy. Conclusion: An accurate history and physical examination and determination of patients with atypical cerebral palsy for doing exome sequencing result in improved genetic counseling and personalized management.